Adverse Childhood Experiences and Pathways to Violent Behavior for Women and Men. Issue 3 (February 2023) - Burke, Catherine; Ellis, Jennifer D.; Peltier, MacKenzie R.; Roberts, Walter; Verplaetse, Terril L.; Phillips, Sarah; Moore, Kelly E.; Marotta, Phillip L.; McKee, Sherry A.
Childhood maltreatment is associated with risk for committing future violence, but the relationship between subgroups and biological sex is unknown. The relationship between adverse childhood experiences (ACEs), violence, and sex was examined using a nationally representative sample. Results from a latent class analysis suggested a four-class model (low adversity; moderate maltreatment with high household dysfunction; severe maltreatment with moderate household dysfunction; severe multi-type adversities). When compared to low adversity, all typology groups were at significantly higher risk to engage in violence (odds ratio > 2.10, p s < .013). The data supported a linear trajectory, meaning increased childhood trauma was associated with increased risk for violence. Although men endorsed more violent behavior, the relationship between ACEs and violence was significantly stronger among women. Prior findings identify that women are more negatively impacted by ACEs and the current findings newly identify that this extends to violent crime.